2019
DOI: 10.33160/yam.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

A Path Model Analysis of the Causal Relationship between Self-care Agency and Healthy Behavior in Community-dwelling Older People from the GAINA Study

Abstract: Background Self-care agency is an important determinant of self-care behavior. The purpose of this study was to identify the causal relationship between self-care agency and healthy behavior, and to construct a conceptual model of healthy behavior among older people living in a rural community. Methods This study was conducted as a crosssectional survey at the Hino, a town in western Tottori Prefecture, Japan. Participants who were enrolled in the Good Ageing and Intervention against Nursing Care and Activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The present study revealed that 4 factors were important to maintaining the care for oneself among certificate nursing assistant students, including also the acquisition and performance of different activities that can be considered as necessary to achieve and promote well-being. In regard to other recent studies performing path analysis of ‘self-care agency’, we find the Turkish validity of the scale [ 50 ], and the study of Tanimura [ 51 ] identified a causal relationship between ASAS and healthy behavior among community-dwelling elder people in Japan and confirmed the potential to adopt positive and proactive healthier behaviors if people acquire ‘self-care agency’. Waki [ 52 ] used an adaptation of ASAS and found that a ‘body self-awareness’ served as an intermediary factor that enabled the performance of self-care operations by making the most use of self-care agency.…”
Section: Discussionsupporting
confidence: 69%
“…The present study revealed that 4 factors were important to maintaining the care for oneself among certificate nursing assistant students, including also the acquisition and performance of different activities that can be considered as necessary to achieve and promote well-being. In regard to other recent studies performing path analysis of ‘self-care agency’, we find the Turkish validity of the scale [ 50 ], and the study of Tanimura [ 51 ] identified a causal relationship between ASAS and healthy behavior among community-dwelling elder people in Japan and confirmed the potential to adopt positive and proactive healthier behaviors if people acquire ‘self-care agency’. Waki [ 52 ] used an adaptation of ASAS and found that a ‘body self-awareness’ served as an intermediary factor that enabled the performance of self-care operations by making the most use of self-care agency.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, this is an issue which has already been studied in different contexts, with several studies showing statistically significant associations between self-care ability, health promotion behaviours and well-being in the elderly. 5,6,7,8 The relevance of the dimension of self-care in a health context is also highlighted by the increasing number of studies providing instruments to assess the self-care ability of elderly people, 9,10 allowing to objectify their needs associated with the diversity of events that occur throughout the course of life, and not only as a direct result of chronological age, 11 and contribute to the development of interventions that respond to the individuality of the person's life. In this line of thought, the most recent world report on ageing and health presents a social approach to address this issue, 11 highlighting that advanced age does not imply dependence and that, although most elderly people coexist with multiple comorbidities, the diversity of their capacities and needs is not random.…”
Section: Introductionmentioning
confidence: 99%
“…Self-care is an important concept, including personal responsibilities varying from preventing impairment of health to promoting health and protecting the psychological well-being of the individual (Tanimura et al, 2019 ). The concept of self-care was first introduced by Orem in 1959.…”
Section: Introductionmentioning
confidence: 99%